Exploring the relationship between vulnerability and adaptation of rural households: disaster resettlement experience from rural China - Liu, Wei; Duan, Mingfei; Feldman, Marcus (Frontiers in Environmental Science, 2024)
In the face of environmental deterioration and to improve human welfare, China’s Shaanxi provincial government has launched one of the largest disaster shelter and resettlement projects in history. In assessing the likely success of this project, it is important to measure the vulnerability and adaptation of rural households in areas where the population experiences ecological and livelihood vulnerability. Based on 657 rural questionnaires collected in southern Shaanxi relocation zones, this study explores four categories of relationship between vulnerability and adaptation based on two aspects of livelihood resilience, namely specific resilience and general resilience. A multinomial logistic regression model is employed to investigate the influence of disaster resettlement on these categories. The analysis finds that: (1) there is a connection between these categories and household livelihood strategies, and rural households are more likely to adopt non-agricultural strategy or livelihood diversification strategy; (2) the livelihood resilience of relocated households is significantly higher than that of non-relocated household, with specific resilience being the main reason for the difference; (3) participation in disaster resettlement, centralized resettlement, and high relocation subsidies are not conducive to belonging in the “low vulnerability–high adaptation” category, while voluntary relocation is conducive to being in this category. These results have significant ramifications for China and other developing national disaster resettlement programs. It is critical for resettled households to reduce livelihood vulnerability and improve adaptive capacity.